The ability of the NiSOD binding loop to chelate zinc(ii): the role of the terminal amino group in the enzymatic functions. Issue 18 (15th April 2019) - Csire, Gizella; Kolozsi, András; Gajda, Tamás; Pappalardo, Giuseppe; Várnagy, Katalin; Sóvágó, Imre; Fábián, István; Lihi, Norbert
Abstract : Equilibrium and spectroscopic characterization of zinc(ii ) complexes with NiSOD related peptides highlights the crucial role of terminal amino groups in the enzymatic function. Abstract : Equilibrium and detailed spectroscopic characterization of zinc(ii ) complexes with NiSOD binding loop and their related model fragments are reported in the whole investigated pH-range. The zinc(ii ) complexes ofL1 (HCDLPCGVY-NH2 ), L2 (Ac-HCDLPCGVY-NH2 ) andL3 (HCDLACGVY-NH2 ) and the nickel(ii ) and zinc(ii ) complexes ofL4 (HCDLPCG-NH2 ) were studied by pH-potentiometric and several spectroscopic methods. The results indicated that the macrochelate coordinated zinc(ii ) complexes are dominant in a whole pH-range and the side chain donors of the peptides are involved in the metal binding. Therefore, the deprotonation and coordination of the peptide backbone occur only in a strongly alkaline solution. The acetylation of the peptide amino terminus (L2 ) significantly enhances the zinc(ii ) binding ability compared to the corresponding nickel(ii ) complexes.L2 complexes of zinc(ii ) are 2 or 3 orders of magnitude more stable than the corresponding nickel(ii ) complexes. This effect clearly shows the crucial role of the terminal amino group in the nickel binding for the NiSOD enzyme.